Moving Beyond the Ivory Tower - Bilchik, Shay (Victims & offenders, 2021)
There has been a significant focus over the past two decades on how to best convert research in the field of juvenile justice into effective policy and practice. The growing body of knowledge about evidence-based policies and practices has been accompanied by the need to better understand how to implement them with fidelity, with the ultimate goal of achieving improved outcomes for juvenile justice system-involved youth. Ed Latessa at the University of Cincinnati Corrections Institute (UCCI) has established himself as not only a preeminent researcher, but also as a leader in the corrections field committed to partnering with policymakers and practitioners in an effort to move beyond the ivory tower of academia and connect his research in a meaningful way to the juvenile justice field. This essay provides a brief description of some of the most significant areas of Latessa’s research related to juvenile justice, providing jurisdictional examples of how he engaged policymakers and practitioners across the country to convert that research into real-world applications. It also describes how, under Latessa’s leadership, UCCI has become a leader in supporting the effort to close the gap between what we know and what we do in implementing evidence-based practices in the field.